VARIATIONS IN PRINCIPAL STRESS ORIENTATION AND COULOMB STRESS CHANGES ACCUMULATION ON SUMATRA SUBDUCTION AND SUMATRA FAULT CAUSED BY MEGATHRUST EARTHQUAKES (MW>7.5) B - Taufiq Rafie, Muhammad
Sumatra Island is adjacent to an active plate boundary of oblique convergence between Indian-Australian plate and Sunda plate. This tectonic setting has resulted in the occurrence of many large historical-recorded megathrust earthquakes (Mw>7.5) along Sumatra trench megathrust which have significant effect on the in-situ stress perturbation and stress changes distribution to the nearest fault system, in this case, Great Sumatra Fault (GSF). Stress changes caused by those megathrust earthquakes have a possibility to bring the faults close to failure. In this study, the stress variation for pre- and post-mainshock of 2004-2005 megathrust earthquakes on the Sumatra forearc is investigated using 330 previously published focal mechanisms in outer forearc Sumatrea from June 1976 to August 2017. Also, the stress changes due to megathrust earthquakes is imparted on the GSF using the studied slip models and the increase in tectonic stress rate on the GSF is estimated under the case of no sliver movement and with sliver movement. The results reveal a resolvable coseismic changes in stress orientation in the Sumatra forearc which is in agreement with the previous studies. Spesifically, the stress rotation analysis found evidence for a stress signature of the previously studied rupture barrier beneath the island of Simeulue that separates the 2004 and 2005 earthquake rupture areas. Moreover, it also indicates that the ratio of stress drop for 2004 earthquake is higher than 2005 earthquake. The Coulomb stress of megathrust earthquakes and increase in tectonic stress rate were used to model the stress changes evolution on the GSF. The increase in tectonic stress rate with sliver movement is the most suitable for the GSF because this case fits better with the GPS data and slip rate in the GSF. The analysis from the stress changes evolution model shows high increase in tectonic stress rate indicating that the tectonic stress rate plays dominant role compared to megathrust earthquakes in allowing large inland earthquakes to occur. The evolution of stress changes in GSF also explains that the stress condition on Musi-Manna segments is exceeding the highest stress changes from previous large inland earthquake occurred which increasing their earthquake hazard potentials. This study shows that the occurrence of megathrust earthquakes alters enough the background stress on Sumatran forearc. Moreover, the tectonic stress rate (~17 kPa/year) controls dominantly the shear stress accumulation on the GSF until the fault closer to failure, generating large earthquake. According to this study, a further evalution is necessary for the seismic hazard potential on GSF, particularly on the southern part of the GSF.